Hubungan Kepatuhan Pembatasan Intake Cairan Dengan Kualitas Hidup Pada Pasien Yang Mengalami Hemodialisa Diatas 3 Tahun Di Ruang Hemodialisa Rsud Dr. H. M. Rabain Muara Enim - Gusni, Jufrika; Miswarti, Miswarti; Eni, Rosmi (Initium Medica Journal, 2024)
In South Sumatra Province, there was a significant increase in chronic kidney failure patients, based on distance/mile 2.5 permile in 2013 increasing to 3.8 permile in 2018. Data from the Health Office stated that throughout 2019 there were 461 new cases of kidney failure patients who died from lack of compliance with fluid restriction. Research objectives for The relationship between compliance with fluid intake restriction and quality of life in patients undergoing hemodialysis for more than 3 years at RSUD Dr. H. M. Rabain Muara Enim in 2022. The research data was taken for 2 weeks starting on September 11 to September 24, 2022. The type of research used was descriptive analytic with an analytical survey design using a cross sectional study approach with a sample of 36 people. Data analysis is presented in the form of distribution tables of each dependent and independent variable. The results of this study showed that 47.2% of patients experienced poor quality of life and 33.3% of patients did not comply with the patient's fluid intake restriction. statistical test obtained p value = 0.034 (<0.05) meaning Ha is accepted so that there is a significant relationship between fluid restriction compliance with the patient's quality of life. It is hoped that the hospital leadership can use the results of this study as input or information for hospital leaders in solving the problem of patient non-compliance in limiting fluids and also as basic data in providing educational guidance to patients in carrying out hemodialysis.